2007
DOI: 10.2495/eco070201
|View full text |Cite
|
Sign up to set email alerts
|

GIS based land use planning and watershed monitoring as tools for sustainable development

Abstract: The development of GIS based methodologies supports a program for monitoring the territorial dynamics that are occurring in the Estorãos rural watershed (NW Portugal). GIS integrates spatial databases from different research and development projects, with the purpose of understanding: (i) the relationships between land use processes and changes, and environmental management policies; (ii) the extent of environmental impacts due to forest fire as well as extending and intensifying agriculture; and (iii) the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It was also indicated that forests and water bodies provided the highest overall ES capacity, while the lowest scores were reached in built-up and unused land areas of China [60]. The ES-based studies are not limited to the Chinese context, but have also reported on similar research settings worldwide [63][64][65][66][67].…”
Section: Land Use and Land Cover Considerationsmentioning
confidence: 99%
“…It was also indicated that forests and water bodies provided the highest overall ES capacity, while the lowest scores were reached in built-up and unused land areas of China [60]. The ES-based studies are not limited to the Chinese context, but have also reported on similar research settings worldwide [63][64][65][66][67].…”
Section: Land Use and Land Cover Considerationsmentioning
confidence: 99%
“…They allow a multitude of analyses and interpretations of spatial data to inform local land use planning (Baldwin et al, 2014) and contribute to the implementation of projects and research in the framework of European Programs for Monitoring Natural Habitats (Cojocariu et al, 2018). GIS tools cover a wide range of areas and are useful in management for environmental conservation policies (Joerin and Musy, 2000, Alonso et al, 2007, Marușca, 2019, assessment of soil and water (Mahesh et al, 2007) but also for sustainable agricultural production (Lant et al, 2005;Mendas and Delali, 2012;Zolekar and Bhagat, 2015).…”
Section: Introductionmentioning
confidence: 99%